Evaluation of the combined PBL-CBL teaching method based on Thorndike’s Learning Theory in the education of bacterial resistance detection - Yifeng Liu; Cuiju Mo; Meng Li (Frontiers in Medicine, 2026)
Background Bacterial resistance detection is a core skill for microbiology technicians. Given the limitations of traditional teaching, exploring an efficient novel method is crucial for improving medical interns’ training quality in this field. This study investigates the effects of the combined PBL-CBL teaching method guided by Thorndike’s Learning Theory on bacterial resistance detection education. Methods Medical interns from the Microbiology Section, Department of Laboratory Medicine, The First Affiliated Hospital of Guangxi Medical University, from August 2024 to August 2025, were enrolled and then divided into a control group (receiving the traditional teaching method) and an experimental group (receiving the combined teaching method). Pre- and post-intervention comparisons included professional knowledge scores, critical thinking (measured by the CTDI-CV scale), learning fatigue (measured by the MBI scale), and teaching effect evaluations. Results The experimental group outperformed the control group in theoretical knowledge, practical skills, and antimicrobial susceptibility report analysis. They also showed stronger cognitive levels (curiosity, open-mindedness, systematic and analytical thinking) with higher CTDI-CV scores, lower emotional exhaustion but higher personal accomplishment on the MBI scale, and better teaching effect evaluations, particularly in the aspects of highlighting key and difficult points, promoting active learning, and enhancing clinical practice skills. All differences were statistically significant. Conclusion For education of bacterial resistance detection, the combined PBL-CBL teaching method guided by Thorndike’s Learning Theory can improve medical interns’ professional knowledge, cultivate critical thinking skills, reduce learning burnout, and eventually achieve favorable teaching outcomes.